Biomimetic synthesis of cerium oxide nanosquares on RGO and their enhanced photocatalytic activities. Issue 2 (15th December 2016) - Qian, Junchao; Cao, Yunyue; Chen, Zhigang; Liu, Chengbao; Lu, Xiaowang
Abstract : A simple biotemplate method was successfully employed to prepare CeO2 SQD functionalized biomorphic RGO composites for use in photocatalytic water splitting. Abstract : Water splitting based on heterogeneous photocatalytic nanomaterials is an attractive approach for generating hydrogen as a clean chemical fuel from solar energy. However, the high defect-induced recombination rate of photoexcited electron–hole pairs and poor photostability have greatly limited the heterophotocatalysts' practical application. Herein, we used a biotemplate method to give reduced graphene oxide (RGO) a remarkable unique bio-porous morphology with significant anti-aggregation of CeO2 square quantum dots (SQDs) when growing them in situ during a simple hydrothermal process. Biomorphic CeO2 SQDs–RGO has higher electrical conductivity and a narrowed band gap due to there being abundant oxygen vacancies, which results in more effective photo-induced charge generation, transfer and separation. The composite is able to act as an active visible light photocatalyst for highly efficient hydrogen generation applications. Such biomimetic designs could inspire immense research in synthesizing materials with a controlled structure and morphology toward achieving novel graphene-based nanocomposite photocatalysts for solar energy conversion.